PENGARUH INDEPENDENSI AUDITOR DAN KOMPETENSI AUDITOR PADA SKEPTISISME PROFESIONAL AUDITOR DAN IMPLIKASINYA TERHADAP KUALITAS AUDIT - Handayani, Komang Ayu Tri; Merkusiwati, Lely Aryani (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
Audit quality is kind of audit application by auditor so that both violation and mistakes on financial report can be disclosed. To reach audit quality, auditor must pay attention about factors that can influence audit quality. The aim of this research is to find out the influence of independenc y and competenc y to auditor professional skepticism and the ir implication to audit quality. The population is all auditor s in public accounting firm in Bali, amounting to 8 3 people with a sample obtained by the 83 auditors. Data were collected by using questionnaire with path analysis. The test result shows that both independency and competency have positive influence to professional skepticism. T est results on the coefficients of path analysis also shows that independency and competency have an influence on audit quality through professional skepticism . Beside that, professional skepticism has positive influence to audit quality.
Keywords: independency, competency, skepticism, audit quality